The impact of multilingual education policy on university language teachers’ professional development - Xu, Hao; Pu, Shi (Círculo de Lingüística Aplicada a la Comunicación, 2020)
This article reports on a case study that investigated language teachers’ perceptions of a newly launched multilingual programme in a Chinese university. Forty-one teachers from the university were interviewed. Data analysis reveals that the teachers perceived the new programme as an administration-dominated initiative that would impact on their teaching practice and research engagements. Particularly, they questioned the viability of its pedagogical innovation, and cast doubt on its implications in terms of what type of knowledge and research would be valued. They also viewed the new programme as a form of institutionalisation, resulting in the reallocation of resources within the university. These perceptions demonstrate how the innovative programme, imposed as a policy initiative, could influence the ecosystem of the whole university and affect its sustainable development.
Keywords: multilingual education; policy; professional development; university language teachers